Biodegradable flame-retardant polyester material for Christmas trees and preparation method of biodegradable flame-retardant polyester material
By blending and extruding aromatic polyester, aliphatic polyester, polylactic acid-phosphamide copolymer and hydroxide flame retardant, a biodegradable polyester material with good flame retardancy and excellent mechanical properties was prepared, which solved the problem of non-degradable existing materials and poor compatibility of inorganic flame retardants.
Patent Information
- Application Number
- CN202510200935.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing plastic materials for Christmas trees are non-degradable and difficult to recycle. The compatibility of inorganic flame retardants with polyester materials is poor, affecting the mechanical properties of the materials.
Biodegradable flame retardant polyester material is prepared by blending and extrusion process using 70-80 parts by weight of aromatic polyester, 20-30 parts by weight of aliphatic polyester, 8-20 parts by weight of polylactic acid-phosphamide copolymer and 3-6 parts by weight of hydroxide flame retardant.
It has achieved a biodegradable polyester material with good flame retardancy and excellent mechanical properties, which has improved the compatibility and dispersion of inorganic flame retardants and reduced the adverse effects on the mechanical properties of the materials.
Smart Images

Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester materials, in particular to a biodegradable flame-retardant polyester material for Christmas trees and a preparation method thereof. Background Art
[0002] Simulated plastic Christmas trees are one of the important elements of Christmas. The terminal consumer market is mainly in Europe, North America, Southeast Asia and other regions. Most of the simulated plastic Christmas trees and related products are made in China. The raw materials are mainly petroleum-based polymers such as polyethylene and polyvinyl chloride. Christmas trees are disposable consumer products, non-degradable, and difficult to recycle. Every year, discarded products become plastic waste, causing great pollution. Biodegradable materials and related products can be decomposed into carbon dioxide and water in the natural environment under the action of light, water, microorganisms, etc. With the development of the times, the use of biodegradable materials to replace petroleum-based materials is a research trend.
[0003] Polyester materials such as polylactic acid, polyethylene terephthalate PET, polybutylene adipate / terephthalate PBAT, polybutylene succinate-co-terephthalate PBST, etc. have good mechanical strength and biodegradability, and are widely used in plastics, fibers and other products. Adding inorganic flame retardants such as aluminum hydroxide and magnesium hydroxide to polyester materials can improve their flame retardant properties. However, these inorganic flame retardants have poor compatibility with polyester materials, and adding excessive inorganic flame retardants has a great influence on the mechanical properties of the materials. Chinese patent CN118127814B discloses a method for preparing a durable flame retardant and smoke-suppressing polyester fabric, which uses a nano magnesium hydroxide flame retardant modified by cyclic phosphate doping to improve the flame retardant properties of polyester fibers, but the patent does not improve the mechanical properties of polyester materials. Summary of the invention
[0004] (I) Technical problem to be solved: The present invention provides a biodegradable flame-retardant polyester material for Christmas trees which has good flame retardancy, excellent mechanical properties and is biodegradable.
[0005] (II) Technical solution: A biodegradable flame-retardant polyester material for Christmas trees, comprising 70-80 parts by weight of aromatic polyester, 20-30 parts by weight of aliphatic polyester, 8-20 parts by weight of polylactic acid-phosphoramide copolymer, and 3-6 parts by weight of hydroxide flame retardant.
[0006] The preparation method of the biodegradable flame-retardant polyester material for Christmas trees comprises the following steps: adding polylactic acid-phosphoramide copolymer and hydroxide flame retardant into a mixer for mixing, then adding aromatic polyester and aliphatic polyester, adding the mixed materials into a twin-screw extruder, blending, extruding and pelletizing to obtain the biodegradable flame-retardant polyester material for Christmas trees.
[0007] Preferably, the aromatic polyester is any one of polyethylene terephthalate, polybutylene terephthalate, polybutylene adipate / terephthalate, and polybutylene succinate-co-terephthalate.
[0008] Preferably, the aliphatic polyester is polyglycolide or polylactic acid.
[0009] Preferably, the hydroxide flame retardant is magnesium hydroxide or aluminum hydroxide.
[0010] Preferably, the temperature of sections 1-7 in the twin-screw extruder is 120-180° C., and the screw speed is 150-200 r / min.
[0011] Preferably, the preparation method of polylactic acid-phosphoramide copolymer is: (1) Add 100 parts by weight of 2-bromoethylamine phenyl phosphate, 85-94 parts by weight of 4-hydroxyphthalic anhydride, and 72-84 parts by weight of potassium carbonate to acetonitrile, raise the temperature to 65-75° C., stir and react for 24-48 hours, cool and filter, rotary evaporate the filtrate, and separate by silica gel column chromatography to obtain phthalic anhydride phenyl phosphate intermediate.
[0012] (2) Add 100 parts by weight of polylactic acid diol, 55-60 parts by weight of phthalic anhydride phenyl phosphate intermediate, and 17-20 parts by weight of pyridine to N,N-dimethylformamide, and stir the mixture at 20-30° C. for 12-18 hours. Pour the solution into ethanol, precipitate, filter, wash with ethanol, and dry to obtain a polylactic acid-phosphoramide copolymer.
[0013] (III) Beneficial technical effects: The present invention uses pyridine as a catalyst to carry out anhydride esterification polymerization reaction of polylactic acid diol and phthalic anhydride phenyl phosphate intermediate to obtain polylactic acid-phosphoramide copolymer, and then uses magnesium hydroxide or aluminum hydroxide as an inorganic flame retardant to blend with aromatic polyesters such as polyethylene terephthalate and aliphatic polyesters such as polylactic acid to obtain biodegradable flame-retardant polyester materials. The polylactic acid-phosphoramide copolymer contains polylactic acid fatty acid polyester chain segments and benzoate (aromatic ester) structures, and has good compatibility with aliphatic polyesters and aromatic polyesters, so that the polylactic acid-phosphoramide copolymer can play the role of a compatibilizer, improve the compatibility between aliphatic polyesters such as polylactic acid and aromatic polyesters such as polyethylene terephthalate, and make the polyester composite material have better mechanical properties.
[0014] The polylactic acid-phosphoramide copolymer of the present invention has a large number of carboxyl groups in the side chain, which can interact with the surface of the magnesium hydroxide or aluminum hydroxide inorganic flame retardant during the blending process, thereby achieving the coating modification of the inorganic flame retardant, improving the compatibility and dispersibility of the inorganic flame retardant in the polyester material, and reducing the adverse effects of the inorganic flame retardant on the mechanical properties of the material. As a result, the polyester material exhibits higher tensile strength and elongation at break.
[0015] The main chain of the polylactic acid-phosphoramide copolymer of the present invention contains a large number of phosphoramide groups to form a nitrogen-phosphorus flame retardant system, which has a synergistic flame retardant effect with magnesium hydroxide and aluminum hydroxide inorganic flame retardants, improves the flame retardant properties of the polyester material, and thus reduces the peak heat release rate and the total heat release amount. DETAILED DESCRIPTION
[0016] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0017] The polylactic acid diol (molecular weight 1000), polylactic acid and polyglycolide of the present invention were purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd. Polyethylene terephthalate and polybutylene terephthalate were purchased from Hubei Huada Fine Chemical Co., Ltd. Polybutylene adipate / terephthalate was purchased from Guangzhou Jiushun New Materials Co., Ltd. Polybutylene succinate-co-terephthalate was purchased from Wuhan Shuer Biotechnology Co., Ltd.
[0018] 2-bromoethylamine phenyl phosphate was prepared according to the method of the literature "Synthesis and Characterization of a Nitrogen-Containing Phosphorus Montmorillonite Flame Retardant". 5.2g of triethylamine was added dropwise to 5g of 2-bromoethylamine hydrobromide, and after stirring, 60mL of acetonitrile solution containing 2.7g of dichlorophenyl phosphate was added dropwise, and the mixture was stirred at 40°C for 6h, filtered, washed with ethanol, and dried to obtain 2-bromoethylamine phenyl phosphate. The structural formula is .
[0019] Embodiment 1: (1) Add 20 g of 2-bromoethylamine phenyl phosphate, 17 g of 4-hydroxyphthalic anhydride, and 14.4 g of potassium carbonate to 400 mL of acetonitrile, heat to 75°C, and stir to react for 24 hours. Condensate and reflux during the reaction. After cooling, filter, rotary evaporate the filtrate, separate by silica gel column chromatography, and elute with petroleum ether and ethyl acetate solution to obtain phthalic anhydride phenyl phosphate intermediate. The reaction formula is: .
[0020] (2) Add 100g of polylactic acid diol, 57g of phthalic anhydride phenyl phosphate intermediate, and 17g of pyridine to 1L of N,N-dimethylformamide, stir and react at 25°C for 18h, pour the solution into ethanol, precipitate, filter, wash with ethanol, and dry to obtain polylactic acid-phosphoramide copolymer. The reaction formula is: .
[0021] (3) Add 0.8 kg of polylactic acid-phosphoramide copolymer and 0.3 kg of magnesium hydroxide into a mixer and mix, then add 8 kg of polyethylene terephthalate and 2 kg of polylactic acid. After mixing, add the materials into a twin-screw extruder. The temperatures of sections 1-7 are 120°C, 145°C, 160°C, 175°C, 180°C, 180°C, and 170°C. The screw speed is 200 r / min. Blending, extrusion, and pelletizing are performed to obtain a biodegradable flame-retardant polyester material for Christmas trees.
[0022] Comparative Example 1: (1) 0.3 kg of magnesium hydroxide, 8 kg of polyethylene terephthalate and 2 kg of polylactic acid are mixed and added into a twin-screw extruder. The temperatures of sections 1-7 are 120°C, 145°C, 160°C, 175°C, 180°C, 180°C and 170°C. The screw speed is 200 r / min. The mixture is blended, extruded and pelletized to obtain a biodegradable flame-retardant polyester material for Christmas trees.
[0023] Comparative Example 2: (1) Add 0.8 kg of polylactic acid diol and 0.3 kg of magnesium hydroxide into a mixer and mix, then add 8 kg of polyethylene terephthalate and 2 kg of polylactic acid. After mixing, add the materials into a twin-screw extruder, the temperatures of sections 1-7 are 120°C, 145°C, 160°C, 175°C, 180°C, 180°C, and 170°C, the screw speed is 200 r / min, blending, extrusion, and pelletizing to obtain a biodegradable flame-retardant polyester material for Christmas trees.
[0024] Comparative Example 3 (1) Add 100 g of polylactic acid diol, 32 g of 4,4'-biphenyl ether dianhydride, and 17 g of pyridine to 1 L of N,N-dimethylformamide, and stir at 25°C for 18 h. Pour the solution into ethanol, precipitate, filter, wash with ethanol, and dry to obtain a polylactic acid copolymer.
[0025] (2) Add 0.8 kg of polylactic acid copolymer and 0.3 kg of magnesium hydroxide into a mixer and mix, then add 8 kg of polyethylene terephthalate and 2 kg of polylactic acid. After mixing, add the materials into a twin-screw extruder. The temperatures of sections 1-7 are 120°C, 145°C, 160°C, 175°C, 180°C, 180°C, and 170°C. The screw speed is 200 r / min. Blending, extrusion, and pelletizing are performed to obtain a biodegradable flame-retardant polyester material for Christmas trees.
[0026] Example 2
[0027] (1) Add 20 g of 2-bromoethylamine phenyl phosphate, 18.8 g of 4-hydroxyphthalic anhydride, and 14.4 g of potassium carbonate to 500 mL of acetonitrile, heat to 65°C, stir and react for 48 hours, cool and filter, rotary evaporate the filtrate, separate by silica gel column chromatography, and elute with petroleum ether and ethyl acetate solution to obtain phthalic anhydride phenyl phosphate intermediate.
[0028] (2) Add 100 g of polylactic acid diol, 60 g of phthalic anhydride phenyl phosphate intermediate, and 20 g of pyridine to 1.5 L of N,N-dimethylformamide, and stir the mixture at 20 °C for 18 h. Pour the solution into ethanol, precipitate, filter, wash with ethanol, and dry to obtain a polylactic acid-phosphoramide copolymer.
[0029] (3) Add 1.2 kg of polylactic acid-phosphoramide copolymer and 0.4 kg of aluminum hydroxide into a mixer and mix, then add 7.5 kg of polybutylene terephthalate and 2.5 kg of polylactic acid. After mixing, add the materials into a twin-screw extruder. The temperatures of sections 1-7 are 120°C, 145°C, 160°C, 175°C, 180°C, 180°C, and 170°C. The screw speed is 150 r / min. Blending, extrusion, and pelletizing are performed to obtain a biodegradable flame-retardant polyester material for Christmas trees.
[0030] Example 3
[0031] (1) To 1 L of N,N-dimethylformamide, 100 g of polylactic acid diol, 55 g of phthalic anhydride phenyl phosphate intermediate (prepared according to the method of Example 1), and 17 g of pyridine were added, and the mixture was stirred at 25° C. for 18 h. The solution was poured into ethanol, and the precipitate was filtered, washed with ethanol, and dried to obtain a polylactic acid-phosphoramide copolymer.
[0032] (2) Add 1.6 kg of polylactic acid-phosphoramide copolymer and 0.5 kg of magnesium hydroxide into a mixer and mix, then add 7 kg of polybutylene adipate / terephthalate and 3 kg of polyglycolide. After mixing, add the materials into a twin-screw extruder. The temperatures of sections 1-7 are 120°C, 145°C, 160°C, 175°C, 180°C, 180°C, and 170°C. The screw speed is 150 r / min. Blending, extrusion, and pelletizing are performed to obtain a biodegradable flame-retardant polyester material for Christmas trees.
[0033] Example 4
[0034] (1) Add 100 g of polylactic acid diol, 55 g of phthalic anhydride phenyl phosphate intermediate (prepared according to the method of Example 1), and 18 g of pyridine to 1 L of N,N-dimethylformamide, and stir the mixture at 30°C for 12 h. Pour the solution into ethanol, precipitate, filter, wash with ethanol, and dry to obtain a polylactic acid-phosphoramide copolymer.
[0035] (2) Add 2 kg of polylactic acid-phosphoramide copolymer and 0.6 kg of magnesium hydroxide into a mixer and mix, then add 7.5 kg of polybutylene succinate-co-butylene terephthalate and 2.5 kg of polylactic acid. After mixing, add the materials into a twin-screw extruder, the temperatures of sections 1-7 are 120°C, 145°C, 160°C, 175°C, 180°C, 180°C, and 170°C, the screw speed is 200 r / min, blending, extrusion, and pelletizing to obtain a biodegradable flame-retardant polyester material for Christmas trees.
[0036] The biodegradable flame-retardant polyester material for Christmas trees was injection molded into specimens using an injection molding machine, and the tensile properties were tested according to GB / T 1040.1-2018 standard.
[0037] The combustion performance of the material was tested by cone calorimeter with a thermal radiation power of 50kW / m 2 The sample size is 80mm×80mm×3mm.
[0038] Table 1 Polyester material performance test
[0039] Compared with Comparative Example 1, Example 1 adds a polylactic acid-phosphoramide copolymer, which contains a polylactic acid fatty acid polyester chain segment and a benzoate (aromatic ester) structure, and has good compatibility with aliphatic polyesters and aromatic polyesters, so that the polylactic acid-phosphoramide copolymer can play the role of a compatibilizer, improve the compatibility between aliphatic polyesters such as polylactic acid and aromatic polyesters such as polyethylene terephthalate, and make the polyester composite material have better mechanical properties. In addition, the side chain of the polylactic acid-phosphoramide copolymer contains a large number of carboxyl groups, which can interact with the surface of the inorganic flame retardant of magnesium hydroxide or aluminum hydroxide during the blending process, thereby achieving the coating modification of the inorganic flame retardant, improving the compatibility and dispersibility of the inorganic flame retardant in the polyester material, and reducing the adverse effects of the inorganic flame retardant on the mechanical properties of the material. As a result, the polyester material exhibits higher tensile strength and elongation at break. At the same time, the main chain of the polylactic acid-phosphoramide copolymer contains a large number of phosphoramide groups, forming a nitrogen-phosphorus flame retardant system, which has a synergistic flame retardant effect with inorganic flame retardants such as magnesium hydroxide, improving the flame retardant properties of the polyester material, thereby reducing the peak heat release rate and total heat release.
[0040] Comparative Example 2 adds polylactic acid diol, which does not contain an aromatic ester structure and has poor compatibility with aromatic polyesters such as polyethylene terephthalate, making it difficult to act as a compatibilizer and unable to improve the compatibility between aliphatic polyesters such as polylactic acid and aromatic polyesters such as polyethylene terephthalate. In addition, polylactic acid diol does not contain a large number of carboxyl groups and is difficult to interact with the surface of magnesium hydroxide or aluminum hydroxide inorganic flame retardants, and is unable to effectively coat and modify the inorganic flame retardant, and does not improve the compatibility between the inorganic flame retardant and the polyester material, resulting in the inorganic flame retardant having a greater influence on the mechanical properties of the polyester material, and the tensile strength and elongation at break of the material are low.
[0041] Comparative Example 3 uses an equimolar amount of 4,4'-biphenyl ether dianhydride to replace the phthalic anhydride phenyl phosphate intermediate. The prepared polylactic acid copolymer contains polylactic acid fatty acid polyester chain segments and benzoate (aromatic ester) structures, which can act as a compatibilizer, improve the compatibility between polylactic acid and polyethylene terephthalate, and the side chain of the polylactic acid copolymer contains a large number of carboxyl groups, which can interact with the surface of the magnesium hydroxide inorganic flame retardant to achieve the coating modification of magnesium hydroxide, improve the compatibility of magnesium hydroxide in polyester materials, reduce the adverse effects of magnesium hydroxide on the mechanical properties of materials, and make the polyester material show higher tensile strength and elongation at break. However, the polylactic acid copolymer does not contain phosphoramide groups and nitrogen-phosphorus flame retardant systems, resulting in a large peak heat release rate and total heat release of the polyester material, and poor flame retardant properties.
[0042] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A biodegradable flame-retardant polyester material for Christmas trees, characterized in that: The invention comprises the following raw materials: 70-80 parts by weight of aromatic polyester, 20-30 parts by weight of aliphatic polyester, 8-20 parts by weight of polylactic acid-phosphoramide copolymer, and 3-6 parts by weight of hydroxide flame retardant; The preparation method of the polylactic acid-phosphoramide copolymer is: (1) Add 2-bromoethylamine phenyl phosphate, 4-hydroxyphthalic anhydride and potassium carbonate to acetonitrile, stir for reaction and filter, rotary evaporate the filtrate and separate by silica gel column chromatography to obtain phthalic anhydride phenyl phosphate intermediate; (2) Add polylactic acid diol, phthalic anhydride phenyl phosphate intermediate and pyridine to N,N-dimethylformamide, stir for reaction and then pour the solution into ethanol to precipitate the precipitate, filter, wash and dry to obtain polylactic acid-phosphoramide copolymer.
2. The biodegradable flame-retardant polyester material for Christmas trees according to claim 1, characterized in that: In the above (1), the amount of 2-bromoethylamine phenyl phosphate is 100 parts by weight, the amount of 4-hydroxyphthalic anhydride is 85-94 parts by weight, and the amount of potassium carbonate is 72-84 parts by weight.
3. The biodegradable flame-retardant polyester material for Christmas trees according to claim 1, characterized in that: The reaction temperature in (1) is 65-75°C and the reaction time is 24-48h.
4. The biodegradable flame-retardant polyester material for Christmas trees according to claim 1, characterized in that: The amount of polylactic acid diol used in (2) is 100 parts by weight, the amount of phthalic anhydride phenyl phosphate intermediate is 55-60 parts by weight, and the amount of pyridine is 17-20 parts by weight.
5. The biodegradable flame-retardant polyester material for Christmas trees according to claim 1, characterized in that: The reaction temperature in (2) is 20-30°C and the reaction time is 12-18h.
6. The biodegradable flame-retardant polyester material for Christmas trees according to claim 1, characterized in that: The aromatic polyester is any one of polyethylene terephthalate, polybutylene terephthalate, polybutylene adipate / terephthalate, and polybutylene succinate-co-terephthalate.
7. The biodegradable flame-retardant polyester material for Christmas trees according to claim 1, characterized in that: The aliphatic polyester is polyglycolide or polylactic acid.
8. The biodegradable flame-retardant polyester material for Christmas trees according to claim 1, characterized in that: The hydroxide flame retardant is magnesium hydroxide or aluminum hydroxide.
9. A method for preparing the biodegradable flame-retardant polyester material for Christmas trees according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: adding polylactic acid-phosphoramide copolymer and hydroxide flame retardant into a mixer for mixing, then adding aromatic polyester and aliphatic polyester, adding the mixed materials into a twin-screw extruder, blending, extruding, and pelletizing to obtain a biodegradable flame retardant polyester material for Christmas trees.
10. The method for preparing the biodegradable flame-retardant polyester material for Christmas trees according to claim 9, characterized in that: The temperature of sections 1 to 7 in the twin-screw extruder is 120-180° C., and the screw speed is 150-200 r / min.
Citation Information
Patent Citations
Preparation method of durable flame retardant and smoke-suppressing polyester fabric
CN118127814B
Flame-retardant anti-ultraviolet PET and preparation method thereof
CN110982051A
Functional bio-based thermoplastic polyurethane composite material and preparation method thereof
CN117143314A
Flame-retardant polyester resin composition and covered electric wire using the same
JP2007045952A
Cited By
Flame-retardant degradable polyester material and preparation method thereof
CN120757998A
A flame-retardant biodegradable polyester material and its preparation method
CN120757998B